A house for the struggle : the Black press and the built environment in Chicago - West, E. James (University of Illinois Press, 2022)
"Buildings once symbolized Chicago's place as the business capital of Black America and a thriving hub for Black media. In this groundbreaking work, E. James West examines the city's Black press through its relationship with the built environment. As a house for the struggle, the buildings of publications like Ebony and the Chicago Defender embodied narratives of racial uplift and community resistance. As political hubs, gallery spaces, and public squares, they served as key sites in the ongoing Black quest for self-respect, independence, and civic identity. At the same time, factors ranging from discriminatory business practices to editorial and corporate ideology prescribed their location, use, and appearance, positioning Black press buildings as sites of both Black possibility and racial constraint. Engaging and innovative, A House for the Struggle reconsiders the Black press's place at the crossroads where aspiration collided with life in one of America's most segregated cities."--